2009
DOI: 10.1111/j.1532-5415.2009.02392.x
|View full text |Cite
|
Sign up to set email alerts
|

High Oxidative Stress Is Correlated with Frailty in Elderly Chinese

Abstract: High oxidative stress, characterized by high serum 8-OHdG level, was independently associated with frailty in the selected sample of elderly Chinese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 31 publications
6
58
0
3
Order By: Relevance
“…57,58 Furthermore, there is a reduction in total body water, loss of taste and smell, reduction in the production of pepsin and hydrochloric acid and a consequent reduction in the ingestion of foods. 59 It should be taken into account that poor nutrition, generally characterized by low weight, predisposes the elderly individual to various complications, such as reduced immunity 60 , functional impairment 61 , frailty syndrome 62 (characterized by involuntary weight loss, exhaustion, weakness, reduction in walking speed and balanced and reduced physical activity) 63 and an increase in morbidity and mortality. 64 There is still a lot of divergence about the cutoff points for the body mass index (BMI) in the elderly population.…”
Section: Nutritional Status and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…57,58 Furthermore, there is a reduction in total body water, loss of taste and smell, reduction in the production of pepsin and hydrochloric acid and a consequent reduction in the ingestion of foods. 59 It should be taken into account that poor nutrition, generally characterized by low weight, predisposes the elderly individual to various complications, such as reduced immunity 60 , functional impairment 61 , frailty syndrome 62 (characterized by involuntary weight loss, exhaustion, weakness, reduction in walking speed and balanced and reduced physical activity) 63 and an increase in morbidity and mortality. 64 There is still a lot of divergence about the cutoff points for the body mass index (BMI) in the elderly population.…”
Section: Nutritional Status and Oxidative Stressmentioning
confidence: 99%
“…79 Recognized as one of the complications of poor nutrition, fragility syndrome has been related to oxidation of DNA bases (8-Oxo--dGuo, a marker for oxidation of purine bases). 62 Examining the products of lipid (hydroperoxides) and protein (protein carbonyl) oxidation, previous research has verified that these plasmatic biomarkers are higher both in elderly individuals as well as the obese (elderly > young; elderly obese > elderly non-obese; elderly obese > young obese). 80 When analyzing the nutritional status, oxidative stress and the occurrence of infections in the elderly long-term residents of institutions in the city of Botucatu (SP), the researcher concluded that low weight, identified in 40% of those institutionalized, was associated with low concentrations of α-tocopherol, albumin, and total serum protein.…”
Section: Nutritional Status and Oxidative Stressmentioning
confidence: 99%
“…The rate of oxidative damage to DNA is generally increased by many factors classically associated with metabolic and aging-related conditions, such as cardiovascular disease and diabetes. DNA oxidative damage is dependent on environmental, metabolic, intracellular, and extracellular factors such as alcohol consumption, smoking, aging, and inflammation (Rozalski et al 2005;Siomek et al 2006;Hussain et al 2007;Wu et al 2009;Noren Hooten et al 2012). …”
Section: Biomarkers Of Dna and Rna As Targets Of Oxidation Nucleotidementioning
confidence: 99%
“…Other individual biomarkers of physiological dysregulations that have been interrogated in human observational studies include pro‐inflammatory cytokines such as C‐reactive proteins (CRPs), interleukin‐6 (IL‐6) and tumor necrosis factor‐α (TNF‐α) (Hubbard, O'Mahony, Savva, Calver, & Woodhouse, 2009; Westbury et al, 2017) and inflammatory glycoproteins in the coagulation cascade such as factor VIII, D‐dimer, tissue plasminogen activator (t‐PAS; Walston et al, 2002), cellular and circulating markers of innate immunity (Leng et al, 2009), oxidative stress (Serviddio et al, 2009; Wu, Shiesh, Kuo, & Lin, 2009), and anemia (Hirani et al, 2016), and low kidney function (Wang & Mitch, 2014). Also, the results tend to be inconsistent for individual biomarkers, whereas the number of biomarker impairments across multiple physiological systems strongly predicted physical frailty (Fried et al, 2009; Gruenewald et al, 2009).…”
Section: Introductionmentioning
confidence: 99%